2023
DOI: 10.1002/adfm.202300042
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency InGaN Red Mini‐LEDs on Sapphire Toward Full‐Color Nitride Displays: Effect of Strain Modulation

Abstract: InGaN red light emitting diode (LED) is one of the crucial bottlenecks that must be broken through to realize high-resolution full-color mini/micro-LED displays. The efficiency of InGaN LEDs drops rapidly as the emission spectra go from blue/green to red range due to the poor quality of high-indium-content InGaN materials. Here, high-performance InGaN red LEDs on sapphire grown by metal-organic chemical vapor deposition through strain modulation are reported. A composite buffer layer is proposed to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In another study on strain modulation, Chen et al 166 optimized the thickness of a low-temperature GaN buffer layer. They found that a thickness of 7 nm produced the highest indium content in the QW, resulting in a peak EQE of about 7.4% at a wavelength of 629 nm, with a chip size of 100 Â 200 lm 2 .…”
Section: Importance Of Growth Conditions Of Ingan Red Lledsmentioning
confidence: 99%
“…In another study on strain modulation, Chen et al 166 optimized the thickness of a low-temperature GaN buffer layer. They found that a thickness of 7 nm produced the highest indium content in the QW, resulting in a peak EQE of about 7.4% at a wavelength of 629 nm, with a chip size of 100 Â 200 lm 2 .…”
Section: Importance Of Growth Conditions Of Ingan Red Lledsmentioning
confidence: 99%
“…Similar to the hybrid NL structure, Chen et al proposed a composite buffer layer consisting of sputter AlN and low-temperature GaN to increase the surface lattice constant of GaN and enhance the indium incorporation efficiency. [27] An efficient InGaN red mini-LED chip with a peak wavelength of 629 nm and an external quantum efficiency of 7.4% was consequently realized.…”
Section: Substrate and Buffer Layermentioning
confidence: 99%
“…[30,[37][38][39][40][41][42]. The EQE of InGaN red microLEDs has already reached 7.4%, demonstrating promise for application soon [43,44]. Blue and green InGaN lasers have also achieved inspiring performances [45,46].…”
Section: Introductionmentioning
confidence: 99%